2012
DOI: 10.5468/kjog.2012.55.1.59
|View full text |Cite
|
Sign up to set email alerts
|

A case of retroperitoneal ectopic pregnancy

Abstract: Ectopic pregnancy is an implantation of the fertilized ovum on a place except the endometrium. Most of the ectopic pregnancies are located at the fallopian tube. Only the 1.4% of ectopic pregnancies are abdominal pregnancies, of which only 15 cases of retroperitoneal pregnancies are reported all over the world. In this case, a 21-year-old woman presented with back pain and amenorrhrea for 5+2 weeks with no past history. During the laparoscopic operation, there was retroperitoneal hematoma which was located bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 18 publications
(6 reference statements)
0
1
0
Order By: Relevance
“…KM can also be used in pregnant women; among pregnant women admitted due to TA sequelae, significant reductions in symptoms (lower back pain, neck pain, and headache) were noted after KM treatments such as acupuncture, cupping, pharmacopuncture, and herbal medicine. [13] Regarding safety, an existing retrospective chart review study reported no serious adverse reactions after KM treatment such as acupuncture, CMT, and pharmacopuncture in pregnant women following TA-related injuries. [14] Moreover, in another cohort study, women who underwent acupuncture therapy during pregnancy showed no significant difference in obstetric outcomes, including premature birth or stillbirth, compared to women in the control group, indicating that acupuncture can be a safe therapeutic approach to relieving discomfort.…”
Section: Introductionmentioning
confidence: 99%
“…KM can also be used in pregnant women; among pregnant women admitted due to TA sequelae, significant reductions in symptoms (lower back pain, neck pain, and headache) were noted after KM treatments such as acupuncture, cupping, pharmacopuncture, and herbal medicine. [13] Regarding safety, an existing retrospective chart review study reported no serious adverse reactions after KM treatment such as acupuncture, CMT, and pharmacopuncture in pregnant women following TA-related injuries. [14] Moreover, in another cohort study, women who underwent acupuncture therapy during pregnancy showed no significant difference in obstetric outcomes, including premature birth or stillbirth, compared to women in the control group, indicating that acupuncture can be a safe therapeutic approach to relieving discomfort.…”
Section: Introductionmentioning
confidence: 99%